PENENTUAN WALI NIKAH BAGI ANAK LUAR KAWIN PRESPEKTIF MAQASHID AL-SHARI’AH - Abdul Rozi; Abd Basit Misbachul Fitri (Journal Khafi : Journal Of Islamic Studies, 2024)
In carrying out its duties, the KUA Kesamben in marriage matters refers to Law no. 1 of 1974 and the Compilation of Islamic Law (KHI), emphasize that a girl born out of wedlock can be a legitimate child for both parents if she is born in a valid marriage. However, if you look at it from a fiqh perspective, illegitimate children are only related to their mother and their mother's family. Indirectly in the Indonesian context, this polemic has implications for the policy of the head of the Kesamben KUA as an officer assigned by the State when he is faced with a case of determining the guardian of an illegitimate child in his area. There are 2 (two) problems in this research, namely: (1) What is the practice of the head of the Kesamben KUA regarding determining marriage guardians for illegitimate children? (2) What is the perspective of Maqashid al-shari`ah regarding the practice of the head of the Kesamben KUA regarding the determination of marriage guardians for illegitimate children? The approach in this research is a juridical-empirical approach, so the type of research used is qualitative research. The method used in this research is the descriptive-analysis method. Meanwhile, when looking at the method of data collection, this research is classified as field research. In simpler language, the data from observations, documentation and interviews will later be narrated, arranged systematically and then analyzed using the Maqashid al-shari>`ah approach. There are 2 (two) conclusions in this research. First, the practice of determining the guardian of an illegitimate child at KUA Kesamben is to first ask for a photocopy of the marriage certificate of both parents. If it turns out that the child was born 6 months after the marriage of his parents, then he may be married by his father or a Kesamben KUA officer. Meanwhile, if he is born less than 6 months after his parents' marriage, the Kesamben KUA will apply as a guardian judge in the child's marriage. Second, the determination of marriage guardians for illegitimate children at KUA Kesamben by the head of KUA Kesamben is in accordance with maqashid al-Syari'ah. Especially in terms of protecting religion (Hifd